Reducing the Carbon Footprint in a Vehicle Routing Problem by Pooling Resources from Different Companies - Parada-Daza, V (Springer New York LLC, 2016)
In this study, we propose that pooling resources would reduce both the carbon footprint and economic costsin the vehicle routing problem with time windows. A mathematical formulation for the vehicle routing problem considering the carbon footprint as a constraint is proposed. The model is approached with the scatter search metaheuristic and analyzed from the perspective of game theory to evaluate the stability of the coalition after pooling. We define a theoretical case for four suppliers on an instance partition from Solomon’s library using several scenarios from individual participation to a full coalition. For each of these scenarios, we realize a sweep of the objective space. The results show that the more resources are shared, the greater the benefit. The best savings and contributions are achieved by operating in complete cooperation. These savings were distributed as fairly as possible to maintain a stable coalition using the Shapley value. © 2015, Springer Science+Business Media New York.